An experimentally-based procedure for residual life assessment of steel radiant tubes. (April 2022) - Giudice, Fabio; Grasso, Antonio; Guglielmino, Eugenio; Sili, Andrea
Abstract: A calculation model is proposed to assess the combined effects of hot oxidation and creep damage on the residual life of radiant tubes used in topping furnaces of petrochemical plants. Experimental measures of thickness loss due to hot oxidation were carried out on specimens made of ASTM A335 P5 steel for tubes, to define the correlation of the thickness reduction with operating temperature and time, which was subsequently applied to evaluate the residual life in creep conditions. The model resulted effective in formulating hypotheses on the tubes actual thermal history, and defining the range of operating conditions that guarantee a safe return to service. It has also proved effective to predict the service life span of new tubes in ideal stable operating temperature, confirming the need for scheduling periodic checks to detect the actual condition of the tubes. Finally, a procedure for decision-making on tube decommissioning in maintenance interventions is presented. Graphical abstract: Image 1 Highlights: A calculation model for residual life of radiant tubes at high temperature is proposed. The relationship between thickness loss and hot corrosion conditions is found. The creep resistance of damaged material is experimentally detected. The accuracy in assessing time to rupture at various operating condition is shown. The potential in predicting the service life span of virgin tubes is also investigated.